Change in the height of Korean children and adolescents: analysis from the Korea National Health and Nutrition Survey II and V - Na Yung Ryoo; Ha Young Shin; Jae Hyun Kim; Jin Soo Moon; Chong Guk Lee (Korean Pediatric Society, 2015)
PurposeThe mean adult height of Koreans has increased since nationwide anthropological measurements began in 1967. The objective of this study was to evaluate differences in heights of Korean late adolescents and young adults within and between the Second and Fifth Korea National Health and Nutrition Examination Surveys (KNHANES II and V).MethodsKoreans aged ≤22 years with available measurements of height were enrolled from the KNHANES surveys (KNHANES II: n=3,372 [1,732 males and 1,640 females]; KNHANES V: n=6,190 [3,198 males and 2,992 females]). Differences in the height of KNHANES respondents within and between surveys were evaluated according to age and sex.ResultsIn KNHANES II, there was no significant difference in height between males aged 17-19 years and those aged 20-22 years (174.3±0.5 cm vs. 174.3±0.6 cm, P=0.995). Females aged 20-22 years were taller than those aged 17-19 years (159.8±0.4 cm vs. 161.0±0.4 cm, P=0.017). Females aged 17-19 years were significantly taller in KNHANES V than in KNHANES II (161.2±0.3 cm vs. 159.8±0.4 cm, P=0.004). Respondents aged 20-22 years were taller in KNHANES V than in KNHANES II, although not significantly so; the difference was 0.3±0.8 cm in males (P=0.721) and 0.5±0.6 cm in females (P=0.386).ConclusionKoreans appear to continue growing even in their late adolescence and early twenties. Consequently, it may be necessary to expand the reference age ranges of the Korean growth chart. Additionally, a longitudinal growth survey is needed to determine growth patterns and secular trend in height among Koreans.